Genetically Modified Organisms (GMOs) and the issue of safety and halal in Malaysia - Ab Rahman, Suhaimi; Abd Rahman, Azmawani; Aliaziz, Muhammad Hafiz (American-Eurasian Network for Scientific Information, 2013)
To achieve its aim to be a developed nation in 2020, Malaysia has envisaged biotechnology as an important field to be focused as a new engine for economic growth. This is evidenced through the introduction of National Biotechnology Policy 2005 where a special focus will be given to the development of agriculture, and industry. Genetically Modified Organisms (GMOs) is one of the products. Much ado has been said to the development of GMOs and most of consumers are very concern on the safety and the halalness of the products. This paper is an attempt to highlight the development of GMOs and some issues that relate to the safety and the halalness of the products in Malaysia. To achieve this objective data was collected from both conventional and Islamic sources. This includes policy papers, rules and regulations that relate to the governance of GMOs in Malaysia, and Shariah materials which include classical literatures as well as current fatwas on the issue. The paper concludes that although some mechanisms have been introduced to govern GMOs in Malaysia there is still lacking on the part of the Shariah standards that can be used as a reference in order to govern the practice of GMOs. It is suggested therefore that Shariah standards be developed so as to be incorporated in the existing mechanisms in order to sure that the products are not only safe but also halal to consumers.